Analysis of codon usage bias of lumpy skin disease virus causing livestock infection - Rahman, Siddiq Ur; Rehman, Hassan Ur; Rahman, Inayat Ur; Rauf, Abdur; Alshammari, Abdulrahman; Alharbi, Metab; Haq, Noor ul; Suleria, Hafiz Ansar Rasul; Raza, Sayed Haidar Abbas (Frontiers in Veterinary Science, 2022)
Lumpy skin disease virus (LSDV) causes lumpy skin disease (LSD) in livestock, which is a double-stranded DNA virus that belongs to the genus Capripoxvirus of the family Poxviridae. LSDV is an important poxvirus that has spread out far and wide to become distributed worldwide. It poses serious health risks to the host and causes considerable negative socioeconomic impact on farmers financially and on cattle by causing ruminant-related diseases. Previous studies explained the population structure of the LSDV within the evolutionary time scale and adaptive evolution. However, it is still unknown and remains enigmatic as to how synonymous codons are used by the LSDV. Here, we used 53 LSDV strains and applied the codon usage bias (CUB) analysis to them. Both the base content and the relative synonymous codon usage (RSCU) analysis revealed that the AT-ended codons were more frequently used in the genome of LSDV. Further low codon usage bias was calculated from the effective number of codons (ENC) value. The neutrality plot analysis suggested that the dominant factor of natural selection played a role in the structuring of CUB in LSDV. Additionally, the results from a comparative analysis suggested that the LSDV has adapted host-specific codon usage patterns to sustain successful replication and transmission chains within hosts (Bos taurus and Homo sapiens). Both natural selection and mutational pressure have an impact on the codon usage patterns of the protein-coding genes in LSDV. This study is important because it has characterized the codon usage pattern in the LSDV genomes and has provided the necessary data for a basic evolutionary study on them.